Autophagy and modular restructuring of metabolism control germline tumor differentiation and proliferation in C. elegans. Issue 3 (3rd March 2016) - Gomes, Ligia C.; Odedra, Devang; Dikic, Ivan; Pohl, Christian
ABSTRACT: Autophagy can act either as a tumor suppressor or as a survival mechanism for established tumors. To understand how autophagy plays this dual role in cancer, in vivo models are required. By using a highly heterogeneous C. elegans germline tumor, we show that autophagy-related proteins are expressed in a specific subset of tumor cells, neurons. Inhibition of autophagy impairs neuronal differentiation and increases tumor cell number, resulting in a shorter life span of animals with tumors, while induction of autophagy extends their life span by impairing tumor proliferation. Fasting of animals with fully developed tumors leads to a doubling of their life span, which depends on modular changes in transcription including switches in transcription factor networks and mitochondrial metabolism. Hence, our results suggest that metabolic restructuring, cell-type specific regulation of autophagy and neuronal differentiation constitute central pathways preventing growth of heterogeneous tumors.